kopi robusta Hidrolisis Limbah Kulit Kopi Robusta Berbantuan Microwave Sebagai Bahan Baku Gula Reduksi - Iriel, Khairur Rahman Ilyas; Mizan, Mizanurafi’ Ghifarhadi Prasiefa; M. Iqbal Samudra (Journal of Biobased Chemicals, 2024)
The hydrolysis process is a process of breaking down substances by reacting using water, the aim is to break down the substance. This research focuses on the hydrolysis process to determine the reducing sugar content of coffee parchment. The method used is microwave-assisted hydrolysis. This method can increase lignin release more effectively than conventional cellulose and hemicellulose hydrolysis methods. The most commonly used hydrolysis to hydrolyze cellulose is acid hydrolysis. This research uses coffee parchment raw material (horn skin) which contains cellulose and hemicellulose with HCl solvent. Hydrolysis with acid concentration is (1, 2, and 3 %), microwave power (150, 300, and 450 W), and time (20, 25, and 30 minutes). In this study, the optimal reducing sugar yield was 8.054 g/mL under the operating conditions of 25 minutes, 3 % HCl concentration, and 450 W microwave power.